Use Patterns for Depletable and Recycleable Resources - Weinstein, Milton C.; Zeckhauser, Richard J. (Review of Economic Studies, 1974)
Milton C. Weinstein, Richard J. Zeckhauser; Use Patterns for Depletable and Recycleable Resources12, The Review of Economic Studies, Volume 41, Issue 5, 1 Decem